2012
DOI: 10.31887/dcns.2012.14.1/jmarewski
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic decision making in medicine

Abstract: Can less information be more helpful when it comes to making medical decisions? Contrary to the common intuition that more information is always better, the use of heuristics can help both physicians and patients to make sound decisions. Heuristics are simple decision strategies that ignore part of the available information, basing decisions on only a few relevant predictors. We discuss: (i) how doctors and patients use heuristics; and (ii) when heuristics outperform information-greedy methods, such as regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(108 citation statements)
references
References 59 publications
1
107
0
Order By: Relevance
“…Heuristics are simple strategies or mental processes and rules that people use to form judgments quickly, make decisions, and find solutions to complex problems. This happens when an individual focuses on the most relevant aspects of a problem or situation to formulate a solution ( Gigerenzer & Gassmeier, 2011 ; Marewski & Gigerenzer, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Heuristics are simple strategies or mental processes and rules that people use to form judgments quickly, make decisions, and find solutions to complex problems. This happens when an individual focuses on the most relevant aspects of a problem or situation to formulate a solution ( Gigerenzer & Gassmeier, 2011 ; Marewski & Gigerenzer, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…These are mental shortcuts that enable them to make decisions and process information more rapidly and based on incomplete, uncertain, or/and peripheral information ( Stroebe, 2011 ). Heuristics have been shown to be part of health practitioners' practice and driven by constraints such as time ( Marewski and Gigerenzer, 2012 ). Moreover, it has been shown that heuristics-based information is less resistant to counter-argument and less predictive of behaviour than systematic processing ( Stroebe, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…People, including physicians, often do not use calculated or rational decision strategies, instead relying on heuristics strategies to make decisions ( 1 , 2 ). Heuristics can reduce the time and effort in decision making but may also lead to systematic cognitive biases in medicine settings ( 3 ).…”
Section: Introductionmentioning
confidence: 99%